Obsessive Compulsive Disorder As Seen In The Main Character Of Every Last Word Novel By Tamara Ireland Stone - Fitri Yani; Samanik Samanik (Faculty of Arts and Education, 2023)
This research aims to analyze Samantha as the main character in the Every Last Word novel who suffers Obsessive Compulsive Disorder in the novel. The Writer explain the condition of the main character Samantha who suffers this mental issue. Through Samantha’s daily activities, the author describes the main character got the uncontrolled thought in her life, and she could not handle every details thought in her mind.In this study, the writer uses descriptive qualitative methods to describe the issue inside the novel. This thesis applies psychological approach to describe behavior of the main character that are identified as the symptoms of obsessive compulsive disorder in Every last word by Tamara Ireland Stone. This thesis uses Obsessive Compulsive theory. In OCD there are several symptoms, such as: Unpleasant thought, feeling of doubt, inability to control the mind, fear of the bad thought, feeling of worry, thinking about thought really happened and Small think can make worries.This study shows that the main character is clearly shows symptom of person who suffers Obsessive Compulsive Disorder. This seen from the daily activities. The main character shows the behavior that categorized as the symptoms of Worries and Pure Obsession Obsessive Compulsive Disorder.Key words : Every Last Word, Obsessive Compulsive Disorder, Tamara Ireland Stone